2021
DOI: 10.1021/acsami.1c08056
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Three Buckling-Based Methods to Measure the Elastic Modulus of Nanobiocomposite Thin Films

Abstract: To engineer tunable thin film materials, accurate measurement of their mechanical properties is crucial.However, characterizing the elastic modulus with current methods is particularly challenging for sub-micrometer thick films and hygroscopic materials because they are highly sensitive to environmental conditions and most methods require free-standing films which are difficult to prepare. In this work, we directly compared three buckling-based methods to determine the elastic moduli of supported thin films: 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
(194 reference statements)
0
5
0
Order By: Relevance
“…It is worth noting that no previous work has reported such high Young’s moduli for CNC-reinforced PVOH films or coatingsvalues are usually in the range of several GPa. ,, However, the literature does not report mechanical properties of CNC-reinforced PVOH coatings measured by SIEBIMM, and as mentioned earlier, a comparison of absolute elastic moduli determined by different techniques on materials prepared in different ways is challenging. We have shown that a variety of film buckling/structuring methods all give similar moduli and that, for example, the values are similar to those obtained from AFM modulus mapping . Furthermore, for PVOH-based materials, characterization is often performed on thicker (freestanding) samples using conventional methods.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…It is worth noting that no previous work has reported such high Young’s moduli for CNC-reinforced PVOH films or coatingsvalues are usually in the range of several GPa. ,, However, the literature does not report mechanical properties of CNC-reinforced PVOH coatings measured by SIEBIMM, and as mentioned earlier, a comparison of absolute elastic moduli determined by different techniques on materials prepared in different ways is challenging. We have shown that a variety of film buckling/structuring methods all give similar moduli and that, for example, the values are similar to those obtained from AFM modulus mapping . Furthermore, for PVOH-based materials, characterization is often performed on thicker (freestanding) samples using conventional methods.…”
Section: Resultsmentioning
confidence: 56%
“…These studies have demonstrated that the Young’s modulus of various polymer thin films can be improved by the addition of nanofillers, , inducing chemical cross-linking within the polymer matrix, , controlling the polymer composition, or even altering the architecture of the films . Additionally, SIEBIMM has been implemented to investigate the effect of nanofiller loading and film deposition technique on the mechanical properties of polymer thin films. However, all of these studies were carried out on polymeric thin films with thicknesses under 400 nm, as opposed to the micrometer thick coatings demonstrated here …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, SEM characterization of Graft-then-Shrink dry surfaces with 25 and 60 kDa PCB showed increased heterogeneity in Au layer wrinkled pattern sizes with islands of large micrometer-scale wrinkles surrounded by nanoscale wrinkling (Figure e,f). These unique wrinkled Au structures may indicate increased film stiffness, as the modulus of the rigid skin material determines the wrinkle size, , which may be due to interchain polymer interactions during the shrinking process. No change in Au wrinkling was observed on the 10 kDa PCB Graft-then-Shrink discs, indicating a reduced impact from polymer interchain interactions on stiffness due to the polymer’s smaller MW.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of the photoresist layer increased the wrinkle size compared to wrinkles formed on 20 nm-thick gold films deposited directly onto the PS substrate. This is because the wavelength of the wrinkles is proportional to the combined thickness of the stiff film and the sacrificial layer, and because the sacrificial layer can soften and flow during the shrinking process [11,16,17]. Shrunken electrode with no sacrificial layer on PS substrate.…”
Section: Thin Film Transfer With and Without A Sacrificial Layermentioning
confidence: 99%